Balkanian species of the genus Isoperla Banks, 1906 (Plecoptera: Perlodidae) - Murányi, Dávid (Zootaxa, 2011)
Ten taxa of Balkan Isoperla Banks, 1906 are described or redescribed on the basis of SEM studies of the penis, traditional morphological features, and egg structure: I. oxylepis oxylepis (Despax, 1936), I. oxylepis balcanica Raušer, 1962, I. bosnica Aubert, 1964 stat. rev., I. citrina sp. n., I. albanica Aubert, 1964, I. vevcianensis Ikonomov, 1980, I. tripartita tripartita Illies, 1954, I. obliqua Zwick, 1978 stat. n., I. pesici sp. n. and I. autumnalis sp. n. The types and arrangement of scales and sensilla on penial lobes are summarized for West Palaearctic species groups with some preliminary changes in species grouping proposed. An annotated checklist of the Balkanian species is given and the known distribution of endemic taxa are depicted on maps. Isoperla oxylepis balcanica and I. vevcianensis are new for the fauna of Albania, while I. bosnica and I. grammatica (Poda, 1761) are new for Montenegro and Greece, respectively. Additional significant new country records are provided for Amphinemura triangularis (Ris, 1902), A. quadrangularis Zwick, 1978, Nemoura caligula Zwick,1978 and Leuctra jahorinensis Kaćanski, 1972.